THE EFFECT OF BODY AWARENESS THERAPY AND AEROBIC EXERCISES ON PAIN AND QUALITY OF LIFE IN THE PATIENTS WITH TENSION TYPE HEADACHE - Sertel, Meral; Bakar, YeÅŸim; ÅžimÅŸek, TÃ¼lay Tarsuslu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
AbstractBackground: This study is to investigate the effect of Body Awareness Therapy (BAT) and Aerobic Exercises on painand quality of life in patients with Tension-Type Headache (TTH). Materials and Method: Sixty individuals withTTH diagnosis who referred Neurologist were incorporated into study. The individuals were randomly grouped into 3as BAT (n=20), aerobic exercise (n=20) and control group (n=20). Pain severity of the individuals was evaluated byVisual Analog Scale (VAS) and pain diary, disability with ache; by Pain Disability Index (PDI) and Headache ImpactTests (HIT) and quality of life was evaluated by SF-36. Subsequent to first assessments, 3 sessions of 60 minutes perweek throughout 6 weeks totally.Results: When the groups were compared at the end of the study, a significant decrease was observed in VAS, PDI andHIT values in the individuals in the BAT and aerobic exercise groups. With the individuals in group BAT and aerobicexercise all parameters of quality of life were observed to be increased significantly.Conclusion: BAT and aerobic exercise programs to be applied on TTH patients were concluded to be important indecreasing the pain, in increasing the quality of life and in reducing pain-related daily constraints of the individuals.